1993
DOI: 10.1210/jcem.76.1.8421078
|View full text |Cite
|
Sign up to set email alerts
|

Progression of uremic hyperparathyroidism involves allelic loss on chromosome 11.

Abstract: In occasional cases of secondary hyperparathyroidism, long term stimulation of the parathyroid glands leads from compensatory to autonomous hyperfunction, and thus, hypercalcemia develops. This clinical entity, named tertiary hyperparathyroidism, is possibly due to the formation of an adenoma in one of the hyperplastic glands. Previous studies have shown that parathyroid adenomas may arise with allelic loss on chromosome 11. We tested for allelic loss at several loci on chromosome 11 in 12 enlarged parathyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…These findings indicated that nodules in the hyperplastic parathyroids ofpatients with uremia consisted predominantly of cells with low levels of VDR, which are hyperactive in regard to proliferation. Moreover, recent reports have shown cellular monoclonalities in the secondary parathyroid hyperplasia of uremia (32,33). Of particular note, Falchetti et al suggest that, even in the same patient, the parathyroid glands show different clonalities, the glands with clonal abnormalities being larger than all the other glands.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that nodules in the hyperplastic parathyroids ofpatients with uremia consisted predominantly of cells with low levels of VDR, which are hyperactive in regard to proliferation. Moreover, recent reports have shown cellular monoclonalities in the secondary parathyroid hyperplasia of uremia (32,33). Of particular note, Falchetti et al suggest that, even in the same patient, the parathyroid glands show different clonalities, the glands with clonal abnormalities being larger than all the other glands.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroups of parathyroid adenomas contain rearrangement of the PRADI /cyclin DI oncogene (34)(35)(36) or exhibit loss of a presumed tumor suppressor gene on llq13 (2) or Ip (37). While PRADI or Ip loci have not been assessed in parathyroid hyperplasia, Falchetti et al (5) found allelic loss of 1lq13 DNA markers, thereby demonstrating monoclonality, in only 2 of 12 uremic parathyroid glands. We found no examples of 1 1q13 allelic loss in 18 informative uremic glands, confirming that loss of a chromosome 11 tumor suppressor gene does not appear to be a common mechanism underlying what we show here to be the frequent development of monoclonal tumors in the setting of uremia.…”
Section: Dna Sample Preparationmentioning
confidence: 99%
“…[18][19][20] 11q13, the MEN1 gene locus, is another spot where LOH has been demonstrated in uremic parathyroid hyperplasia. 10,11) Whether or not MEN1 gene abnormality plays a role in the tumorigenesis of uremic parathyroid hyperplasia has not been studied previously, so unraveling this issue was another purpose of our study. Neither LOH nor somatic mutation in the MEN1 gene was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a MEN1 gene abnormality may play a role in clonal emergence in uremic parathyroid hyperplasia. 10,11) In an attempt to elucidate whether uremic parathyroid hyperplasia is of monoclonal origin and how often monoclonal proliferation is associated with MEN1 gene abnormality, we examined this issue in uremic parathyroid hyperplasia.…”
mentioning
confidence: 99%